Synthesis of nanocrystalline thin films at the organic/aqueous interface - Albrasia, E.; Malik, M. (Libyan Journal of Science &Technology, 2022)
This article provides a review of wet chemical routes for the synthesis of nanocrystalline thin films at liquid/liquid interface. The properties of these films at the interfaces of two immiscible liquids have recently been studied with great interest. The recent developments in this area are highly significant and the growth of films at the liquid/liquid interface has made this technique very attractive. This report will also review the effect of concentration of precursors, the particles size, and the morphology of these films grown at interface.